Pengaruh Manajemen Risiko Terhadap Kinerja Keuangan Pada Industri Perbankan Di Indonesia - Agustuty, Lasty; Praditha, Riza; Hariyanti (STIM-LPI Makassar, 2024)
This research aims to examine the effect of risk management (credit risk, operational risk, liquidity risk and market risk) on financial performance (ROA) in the banking industry in Indonesia. The sample used in this research was 37 banking industries in Indonesia from 2019 -2022. The analysis method used is multiple regression of Eviews data. The research results show that credit risk (NPL), operational risk (BOPO), liquidity risk (LDR), have a negative and significant effect on financial performance (ROA) while market risk (NIM) has a positive and significant effect on financial performance (ROA).